PENGARUH STRES KERJA, KEPUASAN TINGKAT GAJI DAN KEPEMIMPINAN TERHADAP TURNOVER INTENTIONS STAFF AUDITOR DI KANTOR AKUNTAN PUBLIK (STUDI PADA KAP DI JAKARTA DAN BANDUNG) - Tesha Jovi Amany; Azwir Nasir; Rahmiati Idrus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This research aims to investigate the effect of job stress, salaries satisfaction and leadership upon the turnover intentions to auditor who work at Jakarta and Bandung accounting firm.The data was collected by distributing questionnaires to 130 respondents, 124 were returned and 120 questionnaires used for the analysis.respondents who fill out the questionnaires. The data analysis was done by using multiple regression. T test result on job stress is 5.816, with a significance value of 0,000 it means there were positive effect and significant influence on turnover intention. T test result for salaries satisfaction is3.230, with a significance value of 0,002 it means there were positive effect and significant influence on turnover intention. T test result for leadership is-4.162, with a significance value of 0,000 it means there were negative effect and significant influence on turnover intention.Keywords: Job Stress, Salaries Satisfaction, Leadership and Turnover Intentions.